2003
DOI: 10.1021/la035153p
|View full text |Cite
|
Sign up to set email alerts
|

Vapor-Phase Adsorption Kinetics of 1-Decene on H-Terminated Si(100)

Abstract: We have investigated in situ and in real time vapor-phase self-assembly of 1-decene on Si, using attenuated total reflection Fourier transform infrared spectroscopy (ATR-FTIRS). The adsorption of 1-decene on hydrogenated Si(100) results in a decane-terminated hydrophobic surface, indicated by the sessile-drop water contact angle at 107 ± 2°. This maximum contact angle is achieved at 160 °C under 30 mTorr of vapor-phase 1-decene. The fractional surface coverage of decane, calculated from the IR absorbance of C−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 43 publications
(91 reference statements)
1
32
0
Order By: Relevance
“…This formation mechanism has been experimentally confirmed by in‐situ attenuated total reflectance‐Fourier‐transform infrared (ATR‐FTIR) spectroscopic study 17. Although the alkyl monolayer can be prepared using a neat solution of 1‐alkene (or 1‐alkyne) containing a diacyl peroxide initiator at the beginning, this radical reaction also occurs at higher temperatures (>110°C) between hydride‐terminated silicon and 1‐alkene or 1‐alkyne, even in the absence of the initiator 18,19.…”
Section: Six (X = C N O) Linked Monolayersmentioning
confidence: 70%
“…This formation mechanism has been experimentally confirmed by in‐situ attenuated total reflectance‐Fourier‐transform infrared (ATR‐FTIR) spectroscopic study 17. Although the alkyl monolayer can be prepared using a neat solution of 1‐alkene (or 1‐alkyne) containing a diacyl peroxide initiator at the beginning, this radical reaction also occurs at higher temperatures (>110°C) between hydride‐terminated silicon and 1‐alkene or 1‐alkyne, even in the absence of the initiator 18,19.…”
Section: Six (X = C N O) Linked Monolayersmentioning
confidence: 70%
“…Although it was first considered to be due to thermal dissociation of Si-H bonds to form Si radicals, it has been pointed out that the temperature of less than 200 ˚C adopted for the thermal SAM formation was too low to dissociate Si-H bonds. 14) According to the mechanism described above, the formation of Si radicals is the crucial step in the UV activation process to obtain SAM directly attached to Si. Since the bond energy of Si-H is 331 -351 kJ mol -1 , simple arithmetic estimates that UV light with wavelengths shorter than 350 nm is required to perform the efficient homolytic cleavage of a Si-H bond.…”
Section: Introductionmentioning
confidence: 99%
“…The vapor-phase passivation of group IV semiconductors has also been explored and dates back to the early 1960s, whereby Si and Ge were passivated by halides, , a range of organics, , nitrides, and oxynitrides, for example, Degen et al have reported the vapor-phase passivation of Si(100) and Si(111) using short-chain alkynes for nanoelectromechanical systems and microelectromechanical system devices . Kosuri et al have described the adsorption kinetics of 1-decyene on H-terminated Si(100) and Si(111) and also the adsorption kinetics of 1-alkanethiols on Ge(111) surfaces. Takenaka et al have reacted Ge surfaces with vaporized tertiarybutylarsine, which is an arsenic source for Ge doping. , In this report, a facile approach for the vapor-phase passivation of oxide-free, chlorine-terminated Ge(100) using a short-chain alkanethiol (1-hexanethiol) at ambient pressure and low temperature (140 °C) is demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…have described the adsorption kinetics of 1-decyene on Hterminated Si(100) 35 and Si(111) 36 and also the adsorption kinetics of 1-alkanethiols on Ge(111) 37 surfaces. Takenaka et al have reacted Ge surfaces with vaporized tertiarybutylarsine, which is an arsenic source for Ge doping.…”
Section: Introductionmentioning
confidence: 99%